Development of HPTLC method for the estimation of ondansetron hydrochloride in bulk drug and sublingual tablets. Issue 2 (5th October 2011) - Mujtaba, Ali; Kohli, Kanchan; Ali, J.; Baboota, Sanjula
Abstract : A new, simple, rapid, accurate and precise high performance thin layer chromatography (HPTLC) method has been developed for the estimation of ondansetron hydrochloride in bulk and sublingual tablets. The mobile phase composition was chloroform : ethyl acetate : methanol : ammonia (9:5:4:0.1 v / v ). Spectrodensitometric analysis of ondansetron was carried out at 254 nm and a symmetrical, well‐resolved, well‐defined peak was obtained at mean retardation factor (Rf ) 0.52 ± 0.02. The calibration plot was linear in the range 200‐1200 ng/spot and showed good linear relationship with coefficient of regression, R 2 = 0.9952 with respect to peak area. The method was validated according to the guidelines of the International Conference on Harmonization (ICH Q2(R1). The limit of detection and quantitation were 14.83 and 44.92 ng per spot, respectively. The recovery study was carried out by standard addition method and the percentage recovery was found to be 99.34 ± 1.08. Therefore it was concluded that the proposed developed HPTLC method can be applied for identification and quantitative determination of ondansetron in bulk drug and dosage forms. Copyright © 2011 John Wiley & Sons, Ltd.